Kolaborasi Pemerintah dan Masyarakat dalam Upaya Pelestarian Masjid Agung Banten sebagai Warisan Sejarah Islam Nusantara - Angeli Ramadhani; Nadia Khumairatun Nisa; Amealiea Prihatinningsih Malandy’s; Ria Amelia; Azalia Salsabila; Siti Alya Aryanti; Syifa Aulia Ramadhani (Pusat Riset dan Inovasi Nasional, 2026)
The Great Mosque of Banten is a historical heritage that reflects cultural acculturation and the glory of Islam in the Indonesian archipelago. This study aims to analyze the forms of collaboration between the government, local communities, and site managers in preserving the Great Mosque of Banten using the Collaborative Governance theory by Ansell and Gash (2007). A descriptive qualitative approach was applied through interviews, field observations, and document studies conducted in the Great Mosque area. The findings reveal that collaboration among stakeholders has not yet reached optimal levels due to limited communication, trust gaps, and conflicting interests. Nevertheless, functional cooperation has emerged through joint activities in sanitation, security, and tour guide training. Based on the five indicators of the collaborative process, direct communication (face to face dialogue) and trust building remain major challenges, while shared understanding between government agencies, the foundation, and the community has begun to develop. This study highlights the importance of sustainable collaborative governance in preserving the religious, historical, and social values of the Great Mosque of Banten while supporting the welfare of the surrounding community.